A NUMERICAL STUDY REGARDING THE INFLUENCE OF THE LONGITUDINAL EXTENT OF A T-SHAPED CRACK ON THE EIGENFREQUENCY DECREASE OF CANTILEVER BEAMS - Cristian Tufisi; GILBERT-RAINER Gillich (Journal of Engineering Studies and Research)
The paper analyzes the effects of T-shaped cracks in beams regarding the manner in which the frequencies of the bending modes change. We determined the eigenfrequencies of the damaged beam involving the finite element method for five lengths of the branched crack’s longitudinal components and numerous crack locations. This permitted plotting the frequency shifts curves and calculating the relative frequency shifts. Afterward, we extracted the damage patterns for all crack types and one crack position. It was found that the patterns are quite similar, just differing by their amplitudes, thus by normalization the damage severity effect can be suppressed.